Caracterização isotópica de cama de frangos de corte alimentados com farinha de vísceras - Mota, Francine dos Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Países importadores, como os que compõem a União Europeia e Ásia, proíbem o uso de farinhas de origem animal, visando a segurança alimentar. Além disso, certificadoras como a Certified Humane exigem dietas 100% vegetais. Essas exigências impõem à cadeia produtiva um rigoroso controle de ingredientes e métodos de detecção. O uso de probióticos neste estudo teve como objetivo avaliar se sua inclusão na dieta interfere na composição isotópica da cama de aviário. O probiótico incluía cepas de Bacillus subtilis e Bacillus amyloliquefaciens, reconhecidas por melhorar a saúde intestinal e a digestibilidade de nutrientes. Neste contexto, a análise de isótopos estáveis de carbono (δ¹³C) e nitrogênio (δ¹⁵N) surge como uma ferramenta confiável para detectar a inclusão de ingredientes de origem animal nas dietas. Este estudo avaliou a aplicação dessa análise na cama de aviário como método para detectar a inclusão de farinha de vísceras na alimentação das aves. Foram utilizados 400 frangos de corte machos, da linhagem Ross 308 AP, distribuídos em quatro tratamentos: T1 (ração com 4% de farinha de vísceras + probiótico), T2 (ração com 4% de farinha de vísceras), T3 (ração vegetal + probiótico) e T4 (ração vegetal). Foi realizado a análise isotópica por meio de espectômetro de massa, após os 42 dias de criação das aves, para verificar os valores isotópicos de carbono e nitrogênio da cama de frangos de corte. Os resultados apresentaram que, até os 35 dias, a inclusão de probióticos na dieta vegetal resultou em valores isotópicos semelhantes aos observados na cama de frangos de corte que tiveram dietas com farinha de vísceras, o que pode levar a interpretações equivocadas. No entanto, essa interferência não foi mantida até o final do da produção, aos 42 dias. Conclui-se que a análise isotópica é uma análise viável para monitorar a dieta de frangos em cama de aviário, desde que a coleta ocorra em momentos apropriados, como aos 42 dias, contribuindo de forma confiável com programas de rastreabilidade e certificação.

The poultry litter, composed of materials such as pine shavings and rice husks, is widely used in broiler chicken production. In Brazil, the use of animal-derived meals in ruminant feed has been prohibited since 1996 due to sanitary risks, including bovine spongiform encephalopathy (BSE) and other diseases associated with the ingestion of animal-based proteins. Stable isotope analysis of carbon (¹³C) and nitrogen (¹⁵N) is a technique used to detect the inclusion of nonpermitted ingredients in ruminant diets. This methodology allows the identification of the animals’ diet composition, enabling the detection of additional components in feed formulations. Diets containing combinations of corn and soybean meal, poultry by-product meal, and probiotics were used, with the following treatments: T1 (FV+PRO) –food a corn- and soybean meal-based diet with 4% poultry byproduct meal and probiotics; T2 (FV) – food a corn- and soybean meal-based diet with 4% poultry by-product meal and a performanceenhancing additive; T3 (PRO) – food a corn- and soybean meal-based diet without animalbased meal, with probiotics; T4 (CONTROL) – food a corn- and soybean meal-based diet without poultry byproduct meal, with a performance-enhancing additive. The objective of this study was to evaluate the impact of the inclusion of poultry byproduct meal in broiler diets on feed conversion and the isotopic composition of litter, diets, and feed ingredients. The results showed that the isotopic signatures of the litter from birds fed diets containing poultry byproduct meal presented less negative δ¹³C values in the treatments with poultry by-product meal and probiotic, and poultry by-product meal alone, when compared to the probiotic and control treatments, indicating the presence of animal-derived proteins. Similarly, δ¹⁵N values were higher in diets containing poultry by-product meal compared to strictly plant-based diets, allowing for the identification of animal protein inclusion in broiler diets. Furthermore, feed conversion was significantly improved in the treatments containing additives, suggesting greater efficiency in nutrient digestion and absorption. The findings of this study demonstrate that stable isotope analysis is an effective tool for identifying the use of animal-derived meals in poultry feed through litter residues, supporting quality control and food safety. Its application may aid in monitoring poultry production, ensuring compliance with international regulations, and preventing the presence of ned ingredients in the production chain.
Isotopic characterization of broilers' bedding fed with offal meal
Keywords: Certificação; Adulteração de alimentos; Segurança alimentar; Substrato avícola